CRISPR/Cas9, a powerful tool to target human herpesviruses. (23rd December 2016) - van Diemen, Ferdy R.; Lebbink, Robert Jan
Abstract: Over 90% of the adult population is infected with one or multiple herpesviruses. These viruses are characterized by their ability to establish latency, where the host is unable to clear the invader from infected cells resulting in a lifelong infection. Herpesviruses cause a wide variety of (recurrent) diseases such as cold sores, shingles, congenital defects and several malignancies. Although the productive phase of a herpesvirus infection can often be efficiently limited by nucleoside analogs, these drugs are ineffective during a latent herpesvirus infection and are therefore unable to clear herpesviruses from the human host. Advances in genome engineering using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 facilitates virus research and may hold potential to treat or cure previously incurable herpesvirus infections by directly targeting these viruses within infected cells. Here, we review recent applications of the CRISPR/Cas9 system for herpesviral research and discuss the therapeutic potential of the system to treat, or even cure, productive and latent herpesviral infections.